Diversity and pattern of nest preference of bat species at bat-dwelling caves in Gombong Karst, Central Java, Indonesia - FAHMA WIJAYANTI; IBNU MARYANTO (Society for Indonesian Biodiversity, 2017)
Wijayanti F, Maryanto I. 2017 Diversity and pattern of nest preference of bat species at bat-dwelling caves in Gombong Karst, Central Java, Indonesia Biodiversitas 18: 864-874. A study on the diversity of bat species, their community structure and pattern of roosting preference, has been conducted in twelve caves in Gombong Karst, Central Java. Bats were caught at the roosting place during the day. Length, width, and height of cave passage were measured, as well as a number of entrances and cave’s ventilation were also calculated. In addition, microclimate parameters were measured under the bat roosts. Data were analyzed by ANOVA, Redundancy analysis (RDA) and canonical correspondence analysis (CCA). Fifteen species (eleven species of insectivorous bats and four species of fruit bats) were recorded. The result also shows that the length, height, and width of the cave passage influenced the community structure of bats. While the other physical factors, i.e. sound intensity, distance from the cave entrance, temperature, humidity, and light intensity influence the bat nesting preference. Furthermore, there were five groups of bats which have a specific pattern of roosting preference.